Impact of energy management practices on environmental and firm performance: Role of energy audit, energy efficiency and top management commitment - Belgacem, Ines; Gafsi, Nesrine (Edelweiss Applied Science and Technology, 2025)
This study investigates how Energy Management Practices (EMPs) influence environmental and firm performance in Saudi Arabia’s manufacturing SMEs, with a focus on the roles of energy audits (EAs), energy efficiency (EE), and top management commitment (TMC). Data were collected from 594 valid responses through a survey of SME managers and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The research model examined direct, mediating, and moderating effects among EMPs, EAs, EE, environmental performance (EP), and firm performance (FP). EMPs significantly improved EAs, which in turn enhanced EE. EE positively influenced EP, while EMPs directly contributed to FP by reducing costs and optimizing resource use. However, the mediating role of EE between EMPs and EP, as well as the moderating role of TMC, was not supported. EMPs serve as a critical driver of sustainability and competitiveness, though their environmental impact is contingent on complementary organizational and contextual factors. Policymakers should promote mandatory audits, financial incentives, and capacity-building initiatives, while managers should integrate EMPs strategically to balance cost reduction with environmental stewardship.